2018
DOI: 10.3390/ijms19124001
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity Affects Thyroid Cancer Cells during the TEXUS-53 Mission Stronger than Hypergravity

Abstract: Thyroid cancer is the most abundant tumor of the endocrine organs. Poorly differentiated thyroid cancer is still difficult to treat. Human cells exposed to long-term real (r-) and simulated (s-) microgravity (µg) revealed morphological alterations and changes in the expression profile of genes involved in several biological processes. The objective of this study was to examine the effects of short-term µg on poorly differentiated follicular thyroid cancer cells (FTC-133 cell line) resulting from 6 min of expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 75 publications
0
24
2
Order By: Relevance
“…It is plausible that this change occurs because the cells are trying to resist the s-µg conditions and hold onto the ECM, although this does not match the generally unchanged amounts of TLN1 gene expression in our experiment. In contrast to the results of this study, FTC-133 cells exposed to µg showed no change in VCL expression and decreased TLN mRNA [75]. Thus, PC-3 cells and FTC-133 cells show a different regulation of FA gene expression and, possibly, synthesis or secretion of proteins.…”
Section: Changes In the Cytoskeleton And The Extracellular Matrixcontrasting
confidence: 99%
“…It is plausible that this change occurs because the cells are trying to resist the s-µg conditions and hold onto the ECM, although this does not match the generally unchanged amounts of TLN1 gene expression in our experiment. In contrast to the results of this study, FTC-133 cells exposed to µg showed no change in VCL expression and decreased TLN mRNA [75]. Thus, PC-3 cells and FTC-133 cells show a different regulation of FA gene expression and, possibly, synthesis or secretion of proteins.…”
Section: Changes In the Cytoskeleton And The Extracellular Matrixcontrasting
confidence: 99%
“…In particular, a microgravity environment can change the migration and invasion ability of tumor cells . According to reports in the literature, related studies have involved thyroid cancer, breast cancer, gastric cancer, lung cancer, colorectal cancer, leukemia, malignant glioma, liver cancer, and neuroblastoma …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have used multiple time points to simulate the effects of microgravity on cells, whereas others have used a single time point (e.g. 6 min, 1 day, 2 days, 3 days, and 14 days), but all of these studies have found that simulated microgravity has a wide range of effects on a variety of cells. A single time point of 7 days was used in the present study, and there is a contingency in the design of an experiment with a single time point.…”
Section: Discussionmentioning
confidence: 99%
“…The omics technology revealed changes of expression and/or accumulation of adhesion proteins under microgravity in AD and MCS cells as compared to control cells cultured under 1g-conditions [5,6]. Hence, additional information was collected about microgravity-dependent posttranslational modifications [20], including phosphorylation [9,21], ubiquitination [22,23], or isgylation [6,24], and about the intracellular translocation of adhesion proteins [25,26].…”
Section: Introductionmentioning
confidence: 99%